GENDER INEQUALITY INDEX: CALCULATING ANALYSIS - Shaikh Sobiya Ansar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Abstract: Gender inequality remains a persistent issue worldwide. In order to measure and track progress towards gender equality, the Gender Inequality Index (GII) was introduced by the United Nations Development Programme (UNDP) in 2010. The GII is a composite index that measures gender-based inequalities in three dimensions: reproductive health, empowerment, and labor market participation. This paper provides an overview of the methodology used to calculate the GII, including the selection of indicators and the weighting system. We also discuss the strengths and limitations of the GII as a measure of gender inequality, and highlight areas for future research.